Natural products in neurodegenerative diseases: recent advances and future outlook - Nahar, L.; Charoensup, R.; Kalieva, Kulyash; Habibi, E.; Guo, M.; Wang, D.; Kvasnica, M.; Onder, A.; Sarker, S. D. (Frontiers in Pharmacology, 2025)
Neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s are on the rise and pose significant challenges due to the lack of effective treatments. This review critically examines the neuroprotective effects of various natural products derived from plants, marine organisms, and fungi. Natural products have long been used in traditional medicine and are gaining attention in modern drug discovery for their unique properties. The review explains how these natural products can protect neurons by influencing the key biological pathways involved in neurodegeneration. It discusses mechanisms including antioxidant effects, anti-inflammatory actions, modulation of cellular signalling, and support for mitochondrial function. A systematic literature search was conducted to minimize bias and ensure rigorous study selection. Preclinical studies using animal models and cell cultures show that secondary metabolites like polyphenols, alkaloids, and terpenoids can significantly reduce neuronal damage. Some clinical trials have shown promising results. However, challenges such as bioavailability, standardization, and dosage must be addressed to translate these findings into clinical practice. The review also evaluates the potential synergy of combining natural products with conventional treatments, offering a complementary therapeutic approach. Natural products represent a promising avenue for developing innovative treatments for neurodegenerative diseases. The review highlights key research gaps and proposes future directions. Future studies should focus on overcoming existing challenges and refining these natural products to improve their efficacy and safety in clinical settings. The application of existing knowledge has the potential to significantly enhance the quality of life for individuals affected by neurodegenerative diseases.